Age at menarche and menstrual complications: a cross cultural study among hostel students in Tirupati, Chittoor district, Andhra Pradesh, India - Pakala, Chandrasekhar Rao; Gujjula, Sudha (International Journal of Research in Medical Sciences, 2016)
Background: Menarche is an important biological and physiological event, which occur in the lifecycle of every normal female. This is accompanied by many morphological, physiological changes in the body. The age of menarche is generally between 10-16 years. The objectives was to assess the age at menarche and menstrual complications among hostel students during menstrual period. Methods: This is a cross-sectional study in which 326 girl students staying at hostel were selected by retrospective method of recall and were evaluated. The exact date of menarche and also any complications occur during menstruation period like pre menstrual syndrome (PMS), irregular periods, painful periods etc. was noted. Results: In the present study majority of the women attain menstruation at the 14th year of their age (31.0%). The mean menarcheal age was 13.83±1.209 years. It was found that among 18.7% are getting irregular periods, 77.9% reported to have premenstrual symptoms and 31.3% students having a set of symptoms like abdominal or back pain / feeling heaviness of the body this was the major ailment suffered by most of the students. It was reported that 53.4% are having painful periods. Conclusions: Create awareness related to reduce disease burden and poor health outcome associated with poor menstrual complications and self care has to be taken among this group to Promote positive attitudes towards the mean age at menarche and menstruation related problems among the adolescent girls is the need of the hour. Hence, we suggest that health education programs regarding PMS and other menstrual problems must be included in the curriculum of secondary schools to bring down the prevalence of such problems.